2016
DOI: 10.1016/j.joca.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Early commencement of physical therapy in the acute phase following elective lower limb arthroplasty produces favorable outcomes: a systematic review and meta-analysis examining allied health service models

Abstract: Early PT commencement and a weekend service may produce favorable outcomes following LL arthroplasty when baseline LOS is 4 days or more. Redistributing PT resources to commence as early as day of surgery regardless of weekday may accelerate postoperative recovery. Current, high quality research is needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…Polish experts recommended starting rehabilitation already on the day of surgery. Surgeons from all over the world have increasingly emphasized early mobilization, which may produce favorable post-operative outcomes [33,34,35]. Most surgeons (92%) reported that they always recommended their patient a rehabilitation with a physiotherapist after knee arthroscopy, which is now considered as a gold standard and its effectiveness was showed by a number of control studies [36,37,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Polish experts recommended starting rehabilitation already on the day of surgery. Surgeons from all over the world have increasingly emphasized early mobilization, which may produce favorable post-operative outcomes [33,34,35]. Most surgeons (92%) reported that they always recommended their patient a rehabilitation with a physiotherapist after knee arthroscopy, which is now considered as a gold standard and its effectiveness was showed by a number of control studies [36,37,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Polish experts recommended starting rehabilitation on the day of surgery. Surgeons from all over the world have increasingly emphasized early mobilization, which may produce favourable postoperative outcomes [33,34,35]. Most surgeons (92%) reported that they always recommended that their patient undergo rehabilitation with a physiotherapist after knee arthroscopy, which is now considered the gold standard, and its effectiveness has been shown by a number of control studies [36,37,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Patients were likely to start physiotherapy early after surgery and be seen more than once a day. A systematic review by Haas, Sarkies, Bowles, O'Brien, and Haines () of acute primary arthroplasty rehabilitation found commencing physiotherapy on the day of surgery is beneficial and shortens LOS, for those patients and procedures with higher levels of complexity and greater scope for improvement in pain and function. This would describe the RTHR group.…”
Section: Discussionmentioning
confidence: 99%
“…The survey found the majority of RTHR patients received some OT but found no agreement about how this is provided. Haas et al () also suggest there is insufficient evidence about OT provision to draw conclusions about the effects of OT on outcomes after THR and the variability may reflect this uncertainty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation